Synthesis of C70‐Based Fluorophores through Sequential Functionalization to Form Isomerically Pure Multiadducts. (27th January 2017) - Lou, Ning; Li, Yanbang; Gan, Liangbing
Abstract: Selective addition to the C70 cage divides its π‐conjugated system into various smaller π‐conjugated systems with enhanced fluorescent properties. Key reactions include chlorination, methoxylation, ozonation, and Bingel or Bingel–Hirsch reactions. The maximum emission wavelength of the C70 multiadducts ranges from 450 to 655 nm. Among the C70 multiadducts, C70 (OMe)8 (C(COOEt)2 )3 showed the highest quantum yield ( Φ F =0.18) and the largest Δ[ λ max (emission)− λ max (absorption)] (402 nm), with maximum emission at 655 nm.